Do neuromuscular adaptations occur in endurance-trained boys and men? - Cohen, R.; Mitchell, C.; Dotan, R.; Gabriel, D.; Klentrou, P.; Falk, B. (Applied Physiology, Nutrition, and Metabolism, 2010)
Abstract: Most research on the effects of endurance training has focused on endurance training's health-related benefits and metabolic effects in both children and adults. The purpose of this study was to examine the neuromuscular effects of endurance training and to investigate whether they differ in children (9.0-12.9 years) and adults (18.4-35.6 years). Maximal isometric torque, rate of torque development (RTD), rate of muscle activation (Q30), electromechanical delay (EMD), and time to peak torque and peak RTD were determined by isokinetic dynamometry and surface electromyography (EMG) in elbow and knee flexion and extension. The subjects were 12 endurance-trained and 16 untrained boys, and 15 endurance-trained and 20 untrained men. The adults displayed consistently higher peak torque, RTD, and Q30, in both absolute and normalized values, whereas the boys had longer EMD (64.7 ± 17.1 vs. 56.6 ± 15.4 ms) and time to peak RTD (98.5 ± 32.1 vs. 80.4 ± 15.0 ms for boys and men, respectively). Q30, normalized for peak EMG amplitude, was the only observed training effect (1.95 ± 1.16 vs. 1.10 ± 0.67 ms for trained and untrained men, respectively). This effect could not be shown in the boys. The findings show normalized muscle strength and rate of activation to be lower in children compared with adults, regardless of training status. Because the observed higher Q30 values were not matched by corresponding higher performance measures in the trained men, the functional and discriminatory significance of Q30 remains unclear. Endurance training does not appear to affect muscle strength or rate of force development in either men or boys.